Безбедносни политики и концепти - GJurovski, Marjan (Фондација Конрад Аденауер во Република Македонија Факултет за безбедност – Скопје, Универзитет „Св.Климент Охридски” - Битола, 2017)
Security as a concept is a prerequisite for the existence of life - individual and societal, and refers to the absence of threats and protection from them. The understanding of security as an innate interest of each individual and the broader human collectivity - family, society, nation, state, international system, indicates the need to expand the concept of security to these collectivities. In theory, therefore, concepts such as national and international security are formed, and in recent times the concepts of individual, societal and global security, pointing to a significant expansion of new dimensions of security. Security policy is a very complex activity and it is difficult to determine which policy is successful and which one is not. From the multitude of factors which influence the success of developing the security policy in the first place should be put those relating to the objective detection of security-related phenomena, mutual cooperation and coordination between the security institutions. Those responsible, competent and obliged to develop security policies should have at their disposal security information timely and objectively. It will enable them to make real security assessment, to determine the security situation and to predict future security events. A successful or good security policy is the one that is able to resolve the security issues with minimal resources and minimal damage. The contemporary economic, political, legal and cultural conditions in the world determine the need for concerted security policy at world level, and also at the levels of united states or regions, as well as the national state. The content of the security policy is determined or is a “product” of the real situations and the real life in the particular state, region or in the world. It should be in the function of the society, the state and the citizens so as to provide for safe improvement of the overall community relations.
Keywords: security policy, risks, threats, security system, security, concepts, theories